"Active Mathematics"-A Classroom-Based Physical Active Learning Intervention in an Elementary School: An Experimental Pilot Study - Liliana Ramos; Vera Simões; Susana Franco (MDPI AG, 2024)
This experimental pilot study aimed to compare the amount of physical activity (PA) of children in a second-year class of an elementary school that had a mathematics class while performing PA, based on playful math games, with children that had a mathematics class seated in a traditional room, for 12 weeks 1 day/week 45 min/class; furthermore, the other two mathematics regular seated classes were attended equally by both groups, and whether both groups showed similar results concerning mathematics grading was assessed. Children (n = 22) were randomly divided into a control group (CG) and an experimental group (EG). In both groups, the number of steps (PA) was measured with a pedometer, before and during all sessions of the intervention program, and an initial diagnostic and a final assessment mathematics test were carried out. EG significantly improved the amount of PA levels in the intervention program, when compared to CG and to the initial baseline (before the program started), with no significant differences between groups in the results of mathematics grading. The introduction of active classes based on playful maths games increases the amount of PA levels in children, and having one math class per week using PA, instead of seating in a traditional room, does not negatively affect the results in terms of mathematics grading. These positive results can contribute to more approaches, at schools, that combine PA and mathematics content.